2018
DOI: 10.4097/kja.d.17.00084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cerebral state index and bispectral index during desflurane anesthesia

Abstract: BackgroundCerebral state index (CSI) is an anesthesia depth monitor alternative to bispectral index (BIS). Published comparative studies have used propofol or sevoflurane. However, studies using desflurane have not been reported yet. Different volatile anesthetics have different electroencephalography signatures. The performance of CSI may be different in desflurane anesthesia. Therefore, the objective of this study was to compare CSI and BIS during desflurane anesthesia.MethodsThirty-three patients were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Several studies have compared the performance of different EEG-derived monitors and other monitors in the patients. [6,14,22,23] Most of these studies reported comparable prediction probabilities for the different monitor types. In the present study, BIS and PSI yielded similar prediction probabilities for distinguishing the maintenance state from recovery state in children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have compared the performance of different EEG-derived monitors and other monitors in the patients. [6,14,22,23] Most of these studies reported comparable prediction probabilities for the different monitor types. In the present study, BIS and PSI yielded similar prediction probabilities for distinguishing the maintenance state from recovery state in children.…”
Section: Discussionmentioning
confidence: 98%
“…Although BIS was developed with adult EEG data, many studies have utilized the BIS to monitor anesthesia depth in children. [3] Now, we have several EEG-based monitors and indicators (e.g., Entropy, [4] Narcotrrend, [5] cerebral state index (CSI), [6] index of consciousness (IoC), [7] qCON, [8] A-line autoregression index (AAI), [9] brain anesthesia response (BAR) [10] and patient state index (PSI) [11]) in clinical practice. Many studies comparing the performance of these monitors have shown the comparable results between the monitors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the performance of different EEG-derived monitors and other monitors in the patients. [6,14,21,22] Most of these studies reported comparable prediction probabilities for the different monitor types. In the present study, BIS and PSI yielded similar prediction probabilities for distinguishing the steady state from recovery state in children.…”
Section: Discussionmentioning
confidence: 98%
“…[2] Although BIS was developed with adult EEG data, many studies have utilized the BIS to monitor anesthesia depth in children. [3] Now, we have several EEG-based monitors and indicators (e.g., Entropy, [4] Narcotrrend, [5] cerebral state index (CSI), [6] index of consciousness (IoC), [7] qCON, [8] A-line autoregression index (AAI), [9] brain anesthesia response (BAR) [10] and patient state index (PSI) [11]) in clinical practice, exhibiting comparable results in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…This month’s edition of the Korean Journal of Anesthesiology contains a paper focusing on the comparison between cerebral state index (CSI) and bispectral index (BIS) during desflurane anesthesia in which Cho et al [ 1 ] reported that CSI can be used as a good substitute for BIS, regardless of the kind of anesthetic used.…”
mentioning
confidence: 99%